Pengaruh Produksi, Jumlah Penduduk, PDB Dan Kurs Dollar Terhadap Impor Jagung Indonesia - Singgih, Vita Agustarita; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
International trade is one of the important factors to stimulate the economic growth of a country, in the era of globalization and free trade may not stop the influx of foreign products. Imports by Indonesia is one of the government's policy in the field of international trade. One of the commodities imported by Indonesia is corn. The purpose of this study was to determine the effect of production, population, Gross Domestic Product (GDP) and simultaneously US dollar exchange rate on imported maize Indonesia in 1997-2013 and the effect of production, population, Gross Domestic Product ( GDP ) and the US dollar exchange rate partially Indonesia to import maize in 1997-2013 as well as determine which variables are most dominant tehadap Indonesian corn imports in 1997-2013. The analysis technique used in this study is a multiple linear regression analysis. The results show production, population, GDP, and the United States Dollar exchange rate effect simultaneously on corn imports Indonesia in 1997-2013 . This is indicated by the value of F ( 21,685 ) > F ( 3,41 ). Partially, the GDP variable is positive and significant effect on maize imports Indonesia in 1997-2013. While the production variables, the number of people and the United States dollar exchange rate has no effect on corn imports Indonesia in 1997-2013.
Keywords: jumlah penduduk; produk domestik bruto; kurs dollar; impor jagung